Determination of the Carrying Capacity of the Beaches of the District of Mollendo, Islay, Arequipa, Peru - Edwin Fredy, Bocardo–Delgado*; Graciano Alberto Del Carpio Tejada; Trinidad Betty, Paredes de Gómez; Eusebio Walter, Colque Rondón; José Alberto, Fernández Rivera, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is proposed to determine the tourist carrying capacity of the beaches of the district of Mollendo in the Province of Islay Arequipa, Peru. The methodology of Cifuentes (1994) was taken as a basis, a calculation of the physical carrying capacity is made, which is then recalculated through factors to the real carrying capacity and finally the effective carrying capacity; Of the four beaches analyzed, the third Beach has the lowest effective carrying capacity with 48 vacationers, while the first Beach has the highest effective capacity with a total of 858 vacationers; on the other hand, the beach sanitary quality index is determined, determining that the first beach and the second beach reach a level of "healthy" while Catarindo and the third beach are determined as "regularly healthy".